Nursing diagnoses in the period of climacteric and menopause - Ohara , Elisabete Calabuig Chapina; Reis, Beatriz Rocha; Almeida , Dailton Silva de; Silva , Márcia Alves da; Santos, Sheila Moreira dos (Seven Editora, 2023)
INTRODUCTION: The transition from the reproductive to the non-reproductive phase is considered a period with several changes. These changes may be metabolic and hormonal that lead to great reflections in the physiological and psychosocial aspect of this woman's life, that is, she undergoes physical and psychological changes. The symptoms in these phases are connected to biological, psychological and social factors, they present themselves in a unique way, varying according to the personal experiences of each woman. It is important in this non-reproductive phase of the woman that she can receive adequate care according to her needs. OBJECTIVE: To list the main nursing diagnoses, as well as nursing interventions in women's health in climacteric and menopause. METHODOLOGY: This was an integrative literature review; to obtain data collection and selection of articles, the following databases were conducted: Latin American and Caribbean Literature on Health Sciences (LILACS), BDENF nursing (Brazil), Scientific Electronic Library Online (SCIELO) and Ministry of Health. The descriptors were Climacteric, Nursing, Care, Quality of life. The included articles published in full; in Portuguese, English and Spanish; published in the last 05 years and the articles excluded dissertations, theses and that did not answer the guiding question of the research. RESULTS: Applying the established criteria, nineteen (19) scientific articles were obtained for the integrative review. In the nursing consultation, it is possible to list the nursing diagnoses, which will increase women's safety and improve the quality of care. Among the nursing diagnoses we listed: Patterns of altered sexuality; Knowledge deficit; Body image disorder; Disturbance in sleep pattern Low self-esteem; Anxiety; Impaired skin integrity; Altered Comfort Risk for control; ineffective therapeutic regimen; Maintenance of altered health and altered nutrition: risk greater than body needs. FINAL CONSIDERATIONS: The identification of nursing diagnoses contributes to the planning and execution of a nursing care plan directed to each woman, which is fundamental for obtaining better quality care. Some unserious symptoms reported by women in the non-reproductive phase can be relieved by nursing interventions that encourage the change of habits such as quitting smoking, leaving alcohol, blood pressure control, weight control, healthy eating, peaceful sleep, leisure, better self-esteem. DOI:https://doi.org/10.56238/alookdevelopv1-144